Fish community response before and after contemporary timber harvest in an inland Pacific Northwest watershed - J.A. Gravelle; Timothy E. Link; Ashley A. Coble (Forest Ecology and Management, 2026)

Climate controls on seasonal groundwater–stream connectivity in snow-dominated semi-arid headwaters - Grace Peven; Timothy E. Link; Danielle Hare; Glen E. Liston; Jan U.H. Eitel (Journal of Hydrology, 2026)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Heightened sensitivity to high-calorie foods in children at risk for obesity: insights from behavior, neuroimaging, and genetics - Kristina M. Rapuano; Link Tejavibulya; Eda Naz Dinc; Anfei Li; Haley Davis; Rachel Korn; Rudolph L. Leibel; B. Timothy Walsh; Lisa Ranzenhofer; Michael Rosenbaum; B. J. Casey; Laurel Mayer (Brain Imaging and Behavior, 2023)
Pediatric obesity is a major public health concern. Genetic susceptibility and increased availability of energy-dense food are known risk factors for obesity. However, the extent to which these factors jointly bias behavior and neural circuitry towards increased adiposity in children remains unclear. While undergoing fMRI, 108 children (ages 5-11y) performed a food-specific go/no-go task. Participants were instructed to either respond (“go”) or inhibit responding (“no-go”) to images of food or toys. Half of the runs depicted high-calorie foods (e.g., pizza) whereas the other half depicted low-calorie foods (e.g., salad). Children were also genotyped for a DNA polymorphism associated with energy intake and obesity ( FTO rs9939609) to examine the influence of obesity risk on behavioral and brain responses to food. Participants demonstrated differences in behavioral sensitivity to high- and low-calorie food images depending on task demands. Participants were slower but more accurate at detecting high- (relative to low-) calorie foods when responding to a neutral stimulus (i.e., toys) and worse at detecting toys when responding to high-calorie foods. Inhibition failures were accompanied by salience network activity (anterior insula, dorsal anterior cingulate cortex), which was driven by false alarms to food images. Children at a greater genetic risk for obesity (dose-dependent model of the FTO genotype) demonstrated pronounced brain and behavioral relationships such that genetic risk was associated with heightened sensitivity to high-calorie food images and increased anterior insula activity. These findings suggest that high-calorie foods may be particularly salient to children at risk for developing eating habits that promote obesity.

Burning trees in frozen soil: Simulating fire, vegetation, soil, and hydrology in the boreal forests of Alaska - Melissa S. Lucash; Adrienne M. Marshall; Shelby A. Weiss; John W. McNabb; Dmitry J. Nicolsky; Gerald N. Flerchinger; Timothy E. Link; Jason G. Vogel; Robert M. Scheller; Rose Z. Abramoff; Vladimir E. Romanovsky (Ecological Modelling, 2023)

Evaluation of pharmacogenomics and hepatic nuclear imaging–related covariates by population pharmacokinetic models of irinotecan and its metabolites - Zheng Liu; Jennifer H. Martin; Winston Liauw; Sue-Anne McLachlan; Emma Link; Anetta Matera; Michael Thompson; Michael Jefford; Rod J. Hicks; Carleen Cullinane; Athena Hatzimihalis; Ian Campbell; et al. (European Journal of Clinical Pharmacology, 2022)

Climate change literature and information gaps in mountainous headwaters of the Columbia River Basin - Adrienne M. Marshall; Meghan Foard; Courtney M. Cooper; Paris Edwards; Shana L. Hirsch; Micah Russell; Timothy E. Link (Regional Environmental Change, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Five ways to support interdisciplinary work before tenure - Melinda Harm Benson; Christopher D. Lippitt; Ryan Morrison; Barbara Cosens; Jan Boll; Brian C. Chaffin; Alexander K. Fremier; Robert Heinse; Derek Kauneckis; Timothy E. Link; Caroline E. Scruggs; Mark Stone; et al. (Journal of Environmental Studies and Sciences, 2016)

Which design elements of individual quota fisheries help to achieve management objectives? - Michael C Melnychuk; Timothy E Essington; Trevor A Branch; Selina S Heppell; Olaf P Jensen; Jason S Link; Steven J D Martell; Ana M Parma; Anthony D M Smith (Fish and Fisheries, 2016)
Individual quota (IQ) management systems in commercial marine fisheries are highly diverse, differing in the security, durability and exclusivity of the harvesting privilege and the transferability of quota units. This diversity in the degree of harvest rights may influence the effectiveness of IQ fisheries to meet management objectives. We conducted a global meta‐analysis of 167 stocks managed under IQs to test whether the strength of harvest rights impacts the conservation status of stocks in terms of catch, exploitation rate and biomass relative to management targets. We used non‐parametric methods to assess non‐linear relationships and linear regression models to explicitly consider interactions among predictors. Most IQ fisheries consistently met fleet‐wide quota limits (94% of stocks had recent catches below or within 10% of quotas), but only 2/3 of IQ fisheries adhered to sustainable management targets for biomass and exploitation rate (68% of stocks had exploitation rates below or within 10% of targets and 63% of stocks had biomass above or within 10% of biomass targets). Strikingly, when exclusivity of the harvesting privilege was low, exploitation rates depended on whether IQ implementation was industry‐driven (exploitation below targets) or government‐mandated (exploitation above targets). At high levels of exclusivity, exploitation rates converged to just below management targets. Transferability of quota units was associated with stock biomass closer to and slightly above target levels than stocks with non‐transferable quota. However, regional differences had the strongest effect on biomass, suggesting that other management or biological attributes of regional fishery systems have greater influence on marine populations.

Can catch share fisheries better track management targets? - Michael C Melnychuk; Timothy E Essington; Trevor A Branch; Selina S Heppell; Olaf P Jensen; Jason S Link; Steven J D Martell; Ana M Parma; John G Pope; Anthony D M Smith (Fish and Fisheries, 2012)
Fisheries management based on catch shares – divisions of annual fleet‐wide quotas among individuals or groups – has been strongly supported for their economic benefits, but biological consequences have not been rigorously quantified. We used a global meta‐analysis of 345 stocks to assess whether fisheries under catch shares were more likely to track management targets set for sustainable harvest than fisheries managed only by fleet‐wide quota caps or effort controls. We examined three ratios: catch‐to‐quota, current exploitation rate to target exploitation rate and current biomass to target biomass. For each, we calculated the mean response, variation around the target and the frequency of undesirable outcomes with respect to these targets. Regional effects were stronger than any other explanatory variable we examined. After accounting for region, we found the effects of catch shares primarily on catch‐to‐quota ratios: these ratios were less variable over time than in other fisheries. Over‐exploitation occurred in only 9% of stocks under catch shares compared to 13% of stocks under fleet‐wide quota caps. Additionally, over‐exploitation occurred in 41% of stocks under effort controls, suggesting a substantial benefit of quota caps alone. In contrast, there was no evidence for a response in the biomass of exploited populations because of either fleet‐wide quota caps or individual catch shares. Thus, for many fisheries, management controls improve under catch shares in terms of reduced variation in catch around quota targets, but ecological benefits in terms of increased biomass may not be realized by catch shares alone.

Effects of Timber Harvest on Aquatic Macroinvertebrate Community Composition in a Northern Idaho Watershed - John A. Gravelle; Timothy E. Link; Justin R. Broglio; Jeff H. Braatne (Forest Science, 2009)
Annual macroinvertebrate sampling was performed from 1994 to 2005 in the Mica Creek Experimental Watershed in northern Idaho to examine the relationship between contemporary timber harvest practices and the structure and diversity of aquatic macroinvertebrate assemblages. Four years of calibration, 4 years of postroad, and 4 years of postharvest (roads + harvest) data were used to analyze treatment effects. Metrics used to assess change included functional feeding group composition, organism densities, taxa richness indices, species diversity, and sediment tolerance indices. These assessments included changes to three macroinvertebrate taxa commonly used as bioindicators of stream habitat quality: Ephemeroptera (mayflies), Plecoptera (stoneflies), and Trichoptera (caddis flies) (EPT). In relation to pretreatment conditions, there were generally no major changes in functional feeding group composition or species diversity. Increases were observed in overall abundance and EPT abundance, but they largely can be explained by natural population variability. These results suggest that little or no change in macroinvertebrate communities resulted from road construction and timber harvest activities in the watershed. Substantial interannual variability was also observed, suggesting that infrequent biomonitoring may not provide adequate information to assess subtle disturbance effects in watersheds but can be an effective part of a comprehensive watershed monitoring program when coupled with other biotic and abiotic metrics.

Timber Harvest Impacts on Water Yield in the Continental/Maritime Hydroclimatic Region of the United States - Jason A. Hubbart; Timothy E. Link; John A. Gravelle; William J. Elliot (Forest Science, 2007)
The inland Pacific Northwest of the United States is influenced by both maritime and continental hydrometeorogical conditions. To date there are limited studies of hydrologic impacts resulting from contemporary timber harvest in this region. Streamflow data were collected since 1991 at the Mica Creek Experimental Watershed (MCEW) in northern Idaho. Treatments were designed to isolate the effects of road construction and two different harvest practices (50% clearcut, 50% partial cut). The change in water yield was assessed using linear regression and analysis of covariance (ANCOVA). Water yield increased in excess of 270 mm/yr (P < 0.01) after clearcut harvesting, and by more than 140 mm/yr (P < 0.01) after partial cut harvesting. Monthly and seasonal analyses revealed the largest impacts of harvest practices on water yield during the snow deposition and melt season from November through June. Dry season analyses (July through October) indicated negligible water yield increases after treatments. Estimates of evapotranspiration (ET) as the residual of the catchment water balance suggest that ET was reduced by 35% and 14% after clearcut and partial cut harvest, respectively. These results establish a base on which to develop tools for effective watershed management in the northern Idaho continental/maritime hydroclimatic region.